1982
DOI: 10.1126/science.7051285
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum Gametocytes from Culture in Vitro Develop to Sporozoites That Are Infectious to Primates

Abstract: Gametocytes of two strains of the human malaria parasite Plasmodium falciparum have been produced in high density by means of a continuous-flow cultivation system. The gametocytes of these two strains infected a mean of 36 percent and 71 percent, respectively, of Anopheles freeborni mosquitoes that fed on a suspension of red blood cells containing the culture gametocytes. Sporozoites harvested from the infected mosquito salivary glands were infective to the chimpanzee (Pan troglodytes) and the owl monkey (Aotu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 20 publications
(13 reference statements)
0
13
0
Order By: Relevance
“…HB3 is a CQS parasite derived from Honduras. The progenitor of Dd2 was derived from a Laotian patient who failed CQ therapy (Campbell et al ., 1982), and this line also has high‐level resistance to pyrimethamine. Dd2 was cloned from W2‐mef which was selected in the laboratory by mefloquine (MQ).…”
Section: Discussionmentioning
confidence: 99%
“…HB3 is a CQS parasite derived from Honduras. The progenitor of Dd2 was derived from a Laotian patient who failed CQ therapy (Campbell et al ., 1982), and this line also has high‐level resistance to pyrimethamine. Dd2 was cloned from W2‐mef which was selected in the laboratory by mefloquine (MQ).…”
Section: Discussionmentioning
confidence: 99%
“…Potential solutions to these problems, although not necessarily recognized at the time as being related to developing an attenuated sporozoite vaccine, were being reported. In 1975, a method for culturing P. falciparum in vitro was reported [26,27], followed by a method for producing gametocytes from these cultures in 1986 [28]. In 1986, it was reported that humans could be infected by the sporozoites produced in mosquitoes that had fed on these in vitro cultures [29].…”
Section: Developing Vaccine With Nuclear Technologymentioning
confidence: 99%
“…HB3, isolated from Central America (Honduras), represents a “wild-type” parasite sensitive to the quinoline line of drugs [35], while Dd2 was derived from a Laotian patient in whom chloroquine (CQ) therapy failed [36]. Dd2 is also resistant to pyrimethamine, as is typical of multidrug resistant (MDR) parasites.…”
Section: Introductionmentioning
confidence: 99%